New Plants for Florida: Strawberry - Craig Chandler; Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS)
The Florida strawberry industry has continued to grow. There are now approximately 7,000 acres in production, with a crop value approaching $200 million. This growth is being fueled, in part, by new variety releases from the FAES breeding program. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.